Biomechanics of balance - Beretta, Victor Spiandor [UNESP]; dos Santos, Paulo Cezar Rocha; Orcioli-Silva, Diego [UNESP]; Barbieri, Fabio Augusto [UNESP] (Elsevier, 2024)
Adequate balance maintenance is important to performing activities of daily living. Several factors contribute to maintaining balance, including sensory input, neuromuscular control, the interaction between the body and its surroundings, biomechanical constraints, and cognitive processing. Biomechanical constraints are involved in postural control, such as the support base, limits of stability, and muscle strength/activation. Changes in these biomechanical constraints, due to task or the individual conditions, affect the postural stability, balance, and maintenance of the upright position. Moreover, some pathologies, such as Parkinson's disease (PD), lead to exacerbated impairments of biomechanics components involved in postural control, mainly in situations with perturbation, which increases the risk of falls. The current chapter aims to describe the biomechanics concepts of balance in different postural situations (i.e. standing, anticipatory postural adjustments, and reactive postural adjustments). Moreover, we will discuss PD as a ‘model' to study the biomechanics of balance.
Keywords: kinematic; kinetic; movement disorders; Parkinson's disease; Postural control